2022
DOI: 10.1161/hypertensionaha.121.18580
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating Initial Orthostatic Hypotension: Mechanistic Roles of Muscle Contraction Versus Sympathetic Activation

Abstract: Background: Initial orthostatic hypotension (IOH) is defined by a large drop in blood pressure (BP) within 15 s of standing. IOH often presents during an active stand, but not with a passive tilt, suggesting that a muscle activation reflex involving lower body muscles plays an important role. To our knowledge, there is no literature exploring how sympathetic activation affects IOH. We hypothesized involuntary muscle contractions before standing would significantly reduce the drop in BP seen in IOH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
0
8
0
1
Order By: Relevance
“…Previous studies have observed IOH ranging from 15-30% in the general population 31 , suggesting IOH may be more prevalent among patients with PASC. IOH requires an active stand with beat-to-beat hemodynamics for accurate detection 15 , 24 , 32 . Few studies have employed these methods, suggesting underdiagnosis of IOH is likely in patients with PASC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have observed IOH ranging from 15-30% in the general population 31 , suggesting IOH may be more prevalent among patients with PASC. IOH requires an active stand with beat-to-beat hemodynamics for accurate detection 15 , 24 , 32 . Few studies have employed these methods, suggesting underdiagnosis of IOH is likely in patients with PASC.…”
Section: Discussionmentioning
confidence: 99%
“…The hemodynamic criterion for postural orthostatic tachycardia syndrome (POTS) was defined as a HR increase ≥30 bpm within 10 minutes of standing in the absence of OH (POTS HR ) 21 , 23 . Initial orthostatic hypotension (IOH) was defined as a transient SBP drop ≥40mmHg within 15 seconds of standing with recovery within 45 seconds (IOH 40 ) 24 . Inappropriate sinus tachycardia (IST) was assessed as a resting supine HR >100bpm (IST 100 ) 25 .…”
Section: Methodsmentioning
confidence: 99%
“…To address this barrier, discrete and proactive use of maneuvers in provocative situations may improve CPM accessibility to a wider range of patients. Muscle tensing prior to a stand can bolster blood pressure more than tensing after standing and was beneficial in preventing initial orthostatic hypotension; this could perhaps be combined with a classical counter maneuver to provide a further benefit ( 97 ). Dynamic maneuvers may also be of particular benefit as they could better facilitate muscle pumping and can be maintained for longer periods of time (as they incorporate cyclical contraction and relaxation) ( 32 , 34 , 74 , 75 ).…”
Section: Counter Pressure Maneuversmentioning
confidence: 99%
“…CPM have been studied most widely in patients in whom their syncope episodes present with a prominent vascular component; this includes VVS ( 36 , 56 , 63 , 67 , 72 , 73 ), initial orthostatic hypotension ( 55 , 97 ), and populations with neurological causes for syncope such as autonomic failure ( 60 , 61 , 64 , 65 , 68 , 71 , 96 ) or familial dysautonomia ( 62 , 94 ). Of note, community-based trials documenting syncope free survival with CPM have only been performed in VVS ( 35 , 89 , 90 , 96 ).…”
Section: Counter Pressure Maneuversmentioning
confidence: 99%
“…Minute nach dem Aufrichten zurückgeführt werden kann. Die hierdurch verursachten transienten orthostatischen Beschwerden werden in den meisten Fällen gut toleriert oder lassen sich durch ein einfaches Gegenmanöver mit Kontraktion der Muskulatur der unteren Körperhälfte gut unterdrücken 4 . Im Untersuchungsbeispiel der Abb.…”
Section: Unbemerkte Kreislaufschwäche: Fehlende Oder Atypische Neurog...unclassified